Poskození organizmu monoklonálními imunoglobuliny a moznosti lécby. Cást druhá - Adam, Z (Vnitrni lekarstvi, 1993)
Monoclonal immunoglobulins (M-Ig) cause due to their chemical structure and physical properties some pathological manifestations. In the text all skin changes are analyzed which are supposed to be associated with M-Ig. Some light chains form amyloid masses which can damage almost all organs. M-Ig can perhaps enhance also the capillary permeability although their role in the capillary leak syndrome remains obscure.
Keywords: Paraproteinemias; imunoglobuliny; Humans; Immunoglobulins; lidé; paraproteinemie